Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar Pada Bursa Efek Indonesia Periode 2019-2021 - Fahendra Pratama (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This research was conducted to determine what can affect profit growth in pharmaceutical sub-sector companies for 2019-2021. The independent variables used in this research are ROA, DAR, CR, and TATO to determine why companies are experiencing profit growth. This study uses firm size as a moderating variable to determine whether it can strengthen the relationship between the independent variables and earnings growth. Using a purposive sampling technique, the sample in this study used 10 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The data analysis technique used in this study is panel data regression and moderation regression. The results of this study state that ROA and DAR have a positive effect on profit growth. In contrast, the CR and TATO variables do not affect profit growth because profit growth occurs when the assets owned by a company can be put to good use to generate profits. Then the size of the company cannot be a moderating variable in this study because the size of the company does not guarantee profit growth in a company, but rather how the company's ability to manage its assets to generate profits. The results of this study can be used as a comparison or reference for research with similar topics. This study has implications that the level of sales and debt management of a company has an essential role in achieving profit growth.